A randomized controlled trial evaluating the efficacy of a brief computerized anxiety sensitivity reduction intervention for health anxiety. (August 2021) - O'Bryan, Emily M.; McLeish, Alison C.; Norr, Aaron M.; Ely, Sarah; Bass, Zoey; Davies, Carolyn D.; Capron, Daniel W.; Schmidt, Norman B.; Mano, Kristen E. Jastrowski
Highlights: Brief interventions for health anxiety (HA) are needed. Anxiety sensitivity (AS) is a key cognitive-affective vulnerability for HA. A brief, computerized intervention reduced AS among adults with high HA. We observed an indirect effect of treatment on HA through reductions in AS. Abstract: It is estimated that individuals with severe health anxiety (HA) utilize 41 %–78 % more healthcare resources than individuals with identified medical diagnoses. Thus, identifying targets for intervention and prevention efforts for HA that are appropriate for primary care or specialty clinic settings is imperative. The aim of the present investigation was to evaluate the effect of a single-session, computerized anxiety sensitivity (AS) intervention on AS and HA. Participants were 68 university students (79.4 % female; Mage = 19.68) with elevated levels of AS and HA. Participants were randomized to either the AS intervention condition or an active control condition and completed self-report and behavioral follow-up assessments at post-intervention, 1-week follow-up, and 1-month follow-up. Results indicated a significant Time x Condition interaction for ASI-3 at each follow-up assessment (all p s < .001), such that individuals in the active condition exhibited greater reductions in AS compared to the control condition. There was no significant Time x Condition interaction for HA at any follow-up. Mediation analyses revealed a significant indirect effect of Condition on changes in HA through changes in AS. No significant effects were observed for behavioral outcomes. Findings suggest that this intervention successfully reduces AS among those who are high in HA and AS and may indirectly contribute to reductions in HA over time through reductions in AS.